Przedterminowe zwolnienie z kary pozbawienia wolności skazanych za ludobójstwo, zbrodnie przeciwko ludzkości i wojenne na mocy orzeczeń międzynarodowych trybunałów karnych ad hoc oraz ich sukcesora w postaci Mechanizmu Rezydualnego ONZ - Szwejkowska, Małgorzata (Wydawnictwo Uniwersytetu Wrocławskiego, 2021)
In the last decade of the 20th century, a war in the former Yugoslavia broke out, once again making Europe a witness to an armed conflict. Almost at the same time, another local ethnic bloodshed started, but this time in distant Africa — in Rwanda. Both these events included the most horrifying international crimes against humanity: genocide and war crimes. To prosecute the most important commanding figures involved in these conflicts and hold them criminally responsible, two ad hoc United Nations tribunals were created: International Criminal Tribunal for the former Yugoslavia in Hague and International Criminal Tribunal for Rwanda in Arusha. They finished their operation in 2017 and 2015, respectively. The tasks of conducting and completing all ongoing proceedings, including law enforcement, after the completion of their mandates have been entrusted to the UN International Residual Mechanism. One of the crucial assignments of the tribunals and later the Redisual Mechanism was to deal with the request on behalf of the convicted for granting them early release. Although none of the statutes of the aforementioned courts provided any ground for early release, soon it was accepted that both tribunals, as well as their successor, were entitled to proceed despite this issue. As soon as in 2001, the first convict was granted early release, but with no conditions. It is estimated that, to date, more than 2/3 of all convicted by the Tribunals have been released before the termination of their sentence. This should raise the question of how to rehabilitate that kind of offender, convicted of genocide, war crimes, or crimes against humanity, to ensure they do not pose a threat to society anymore. Especially since the offenders serve their punishment outside the country of their origin — meaning, different rules apply according to the domestic law regulation of the state that voluntarily agreed to enforce the sentence. This article analyzes the juridical approach of the tribunals and the Residual Mechanism on the issue of early release of the convicts involved in the armed conflicts in the former Yugoslavia and Rwanda.
Keywords: przedterminowe zwolnienie; ludobójstwo; zbrodnie wojenne; przestępstwa przeciwko ludzkości; Międzynarodowy Trybunał Karny dla byłej Jugosławii; Międzynarodowy Trybunał dla Rwandy; Mechanizm Rezydualny ONZ